1992
DOI: 10.1093/protein/5.3.267
|View full text |Cite
|
Sign up to set email alerts
|

A new protein conjugate that replaces the use of secondary antibodies engineered from the two staphylococcal enzymes protein A and 6-phospho-β-galactosidase

Abstract: The lacG gene encoding the 6-phospho-beta-galactosidase (E.C.3.2.1.85) of Staphylococcus aureus was fused to the protein A gene in the plasmid pRIT2T. Escherichia coli cells containing this plasmid produce a fusion protein with both IgG binding and 6-phospho-beta-galactosidase activities after heat induction. The recombinant gene was overexpressed and the hybrid protein was purified to homogeneity in high yield. The chimeric protein was shown to have almost identical enzymatic characteristics to pure 6-phospho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1993
1993
1999
1999

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The chimeric protein is a useful EL1SA reagent with a unique enzyme activity. The fusion to thc N-terminus showed that this part of the molecule is involved ncithcr in substratc recognition nor in the catalytic site [52]. It is currently attempted to fuse othcr pro-…”
Section: Discussionmentioning
confidence: 99%
“…The chimeric protein is a useful EL1SA reagent with a unique enzyme activity. The fusion to thc N-terminus showed that this part of the molecule is involved ncithcr in substratc recognition nor in the catalytic site [52]. It is currently attempted to fuse othcr pro-…”
Section: Discussionmentioning
confidence: 99%